"What is the point of life?": An interpretative phenomenological analysis of suicide in young menwith first‐episode psychosis. Issue 6 (18th April 2017) - Gajwani, Ruchika; Larkin, Michael; Jackson, Chris
Abstract : Background: Lifetime risk of suicide in first‐episode psychosis far exceeds the general population, with the risk of suicide persisting long after first presentation. There is strong evidence to suggest that women more frequently attempt suicide, while men are at a greater risk of completing suicide. First‐hand experiential evidence is needed in order to better understand men's motives for, and struggles with, suicidality in early psychosis. Methods: Semi‐structured interviews were conducted with 7 participants. The interviews explored each respondent's account of their suicide attempt within the broader context of their life, in relation to their past, present and future. In line with the exploratory, inductive nature of the study, an Interpretative Phenomenological Analysis was used to explore the meaning of suicide attempts in these accounts. Results: Three super‐ordinate themes emerged: Self‐as‐vulnerable (intra‐ and inter‐personal relationships), appraisal of cumulative life events as unbearable and meaning of recovery marked by shared sense of hope and imagery for the future . Conclusions: Young men in the early stages of their treatment are seeking to find meaning for frightening, intrusive experiences with origins which often precede psychosis. These experiences permeate personal identity, relationships and recovery. Suicide was perceived as an escape from this conundrum, and was pursued angrily and impulsively. By contrast, the attainment of hope was marked by sharing one's burden and finding a sense of belonging. Specialized assertive outreach programmes may be beneficial in improving the social inclusion of young men who may be particularly marginalized.